PENGARUH VARIASI TEMPERATUR HEAT TREATMENT TERHADAP KEMAMPUKERASAN BAJA KOMERSIL DENGAN METODE JOMINY TEST - Susilo, Irwan; Yusuf, Yusuf; Ruchiyat, Asep (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2021)
Hardenability is the ability of a material to be hardened to a certain depth by means of heat treatment to formmartensite in the cooling process to achieve a certain hardness. One of the hardenability testing methods is theJominy Test. The specimen is heated at the specified temperature, then cooled by spraying water at one end. Aftertesting with the Jominy test apparatus, its hardness was measured using the hardness test equipment.The testingof Jominy is based on ASTM standard A255. Testing using specimens with a length of 100 mm, diameter25.4 mm as much as 9 pieces. Hardness is measured by the Rockwell Hardness Test method. The test result onspecimen 1 with a final temperature of 700 °c resulted in an average hardness value of 45.51 HRB, on specimen9 with a final temperature of 1100 °c amounting to 47.32 HRB. The higher the end temperature of the heating,the hardness value produced will be relatively higher. The highest average hardness value is in specimen 7 witha heating temperature of 1000 °c by 47.48 HRB.